Endocannabinoidome : the world of endocannabinoids and related mediators - Di Marzo, Vicenzo; Wang, Jenny (Academic Press, an imprint of Elsevier, 2015)
The Endocannabinoidome: The World of Endocannabinoids and Related Mediators is dedicated to the latest research and studies on endocannabinoids and cannabinoid receptors to illustrate their important role in the discovery of new, endocannabinoid-related, lipid mediators. Written by leading experts across different disciplines, this book focuses on the biochemical and anlayticial aspects of novel lipid signals, their pharmacological activities and their potential utilization for the development of new and effective therapeutic strategies. The first book of its kind, The Endocannabinoidome is a meaningful reference for all those involved in experimental efforts to further the development of this field.